KINSHIP FOSTER FAMILY´S SITUATION IN VALENCIA CITY - Molero Mañes, Rosa Josefa; Moral Valderas, Mª José; Albiñana Hernández, Paz; Sabater Barrocal, Yolanda; Sospedra Aguado, Rocío (Anales de Psicología / Annals of Psychology, 2007)
The study reported here explored the characteristics of kinship foster family of in order to offer recommendations for policy and practice. The extended family has long played a role in caring for children whose parents were unable to do so. Although the number of children in kinship care has increased in recent years, this type of protection measure has been received less supervision and fewer services. Results show kinship foster families are usually grandparents, specially grandmothers, 60 years old, pensioners with low incomes, who cared 11 year old children with adapta-tion problems and low academic achievement.